2023
DOI: 10.3390/pathogens12081040
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Real-Time RT-PCR Assays for Detection and Differentiation of Porcine Enteric Coronaviruses

Abstract: It is important to be able to detect and differentiate between distinct porcine enteric coronaviruses that can cause similar diseases. However, the existence of naturally occurring recombinant coronaviruses such as swine enteric coronavirus (SeCoV) can give misleading results with currently used diagnostic methods. Therefore, we have developed and validated three duplex real-time quantitative RT-PCR assays for the simultaneous detection of, and differentiation between, porcine epidemic diarrhea virus (PEDV) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, Lung et al reported a novel automated microarray prototype for streamlining post-PCR processing for simultaneous detection and genotyping of bacteria ( Mycoplasma hyopneumonia , A. pleuropneumoniae, Salmonella choleraesuis , and S. suis ) and viruses (PRRSV, SIV, PCV2, PRCV) [ 27 ]. Real-time PCR’s high specificity and sensitivity have proven advantageous in swift pathogen detection [ 28 ]. However, a multiplex real-time PCR approach for simultaneous detection of PRRSV, PCV2, PCV3, and SS pathogens in pigs is yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lung et al reported a novel automated microarray prototype for streamlining post-PCR processing for simultaneous detection and genotyping of bacteria ( Mycoplasma hyopneumonia , A. pleuropneumoniae, Salmonella choleraesuis , and S. suis ) and viruses (PRRSV, SIV, PCV2, PRCV) [ 27 ]. Real-time PCR’s high specificity and sensitivity have proven advantageous in swift pathogen detection [ 28 ]. However, a multiplex real-time PCR approach for simultaneous detection of PRRSV, PCV2, PCV3, and SS pathogens in pigs is yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the commonly used molecular detection techniques for PEDV, TGEV and PoRVA include RT-PCR, nested RT-PCR, qRT-PCR, reverse transcription loop-mediated isothermal amplification, reverse transcription recombinase-aided amplification, and CRISPR-Cas nucleic acid detection (Marthaler et al, 2014;Areekit et al, 2022;Wu et al, 2022;Lazov et al, 2023;Xia et al, 2024). RT-PCR and nested RT-PCR are not capable of quantitative analysis, and their operation is cumbersome, time-consuming and less sensitive.…”
Section: Discussionmentioning
confidence: 99%